Three essays on corporate finance - Deng, Xin (2012)
This dissertation contains three essays on corporate finance. In Essay one, to assess the importance of corporate social responsibility (CSR) in creating value and encouraging cooperative behavior among stakeholders, I examine the valuation effects of merger announcements on acquirers’ various stakeholders and on their behavior in related to proposed merger deals. I find that shareholders, bondholders, suppliers, and major customers of high CSR acquirers as well as target shareholders of these acquirers in stock-swap mergers realize higher merger announcement returns than those of low CSR acquirers. Compared to low CSR acquirers, high CSR acquirers also realize higher announcement returns of the value-weighted portfolio of the acquirer and the target, larger increases in post-merger stock return and operating performance, greater reductions in post-merger cost of capital, and smaller reductions in post-merger number of employees. I also find that mergers by high CSR acquirers take less time to complete, are less likely to fail, and are less likely to be challenged by antitrust authorities than those by low CSR acquirers. These results suggest that CSR benefits both a firm’s shareholders and its other relevant stakeholders and support the stakeholder value maximization view of stakeholder theory.